Higher education in post-modern society: propagation and commercialization of education in the EAD modality in Brazil (Research, Society and Development, 2021)
The article presents the context and trajectory, as well as an analysis of the social problem of higher education in Brazil, based on a study on the commodification and propagation of distance education in the country and the possible influences on learning, arising from the characteristics of the post-modern society. For that, a bibliographical research was carried out, in which a survey of some theoretical references published in written and electronic means was carried out, aiming to collect information and previous knowledge about several positions regarding the investigated theme. The investigation highlighted the main characteristics and the most significant changes that altered and consolidated the transition from an educational scenario, which had a predominantly nationalized and presential configuration, to a reality of commodification of education, which spread in postmodern society through the expansion the offer of higher education, above all, distance learning.